Entre présence et distance sous contrainte, quelle perception par les étudiants des ressources pédagogiques ? - Sophie Kennel (Centre National d'Enseignement à Distance, 2021)
Our present research investigates the uses and students’ perception of the effectiveness of educational material made available by French higher education teachers during the period of pedagogical continuity of spring 2020 to respond to the difficulties encountered in a heterogeneous manner by the student group. After having drawn up a state of the publications of research and current dynamics, we present a survey conducted among students from the University of Strasbourg, from which 3,662 responses were extracted. The purpose was to identify the types of difficulties and the contribution of the resources offered to the learners as well as the effectiveness perceived by the beneficiaries. Our results show the favourable but differentiated effect of the entire pedagogical continuity system to partially overcome the difficulties mentioned by the students who consider the resources beneficial but would have liked a stronger and more explicit educational relationship. This perception is less marked by the disciplinary matrix than by the level of studies. The comparison of our results with previous existing work calls for an integrated approach accompanied by the educational resource in the educational engineering process.